Prioritizing management strategies to achieve multiple outcomes in a globally significant Indonesian protected area. Issue 6 (1st May 2020) - Utami, Ni Wayan Febriana; Wirawan, I Gede Putu; Firn, Jennifer; Kepakisan, Agus Ngurah Krisna; Kusdyana, I Putu Gede Arya; Nicol, Sam; Carwardine, Josie
Abstract: The multiple values delivered by protected areas around the world are threatened and in decline. We propose a structured decision science prioritization approach for justifying and guiding increased investments in protected area management to improve outcomes for a suite of important values. Using Bali's only national park, Taman Nasional Bali Barat (TNBB) as a case study, we draw from existing park documentation and 80 participating experts in TNBB's ecology, society and management to define goals that describe a successful outcome for nine core values of the park: threatened species, ecosystem function, ecosystem habitats, scientific research, food and health, spiritual values, traditional fishing, community prosperity, and ecotourism. Participants estimated that without increased investment, the extent of goal achievement is likely to be below 30% for all values at the end of the 15‐year planning time frame. However, implementing nine strategies, at an increased annual investment of 5.5 billion Indonesian rupiah (US$385, 666) per year, would achieve the goals for all values. The most cost‐effective strategies were predicted to be collaboration and planning, monitoring and managing invasive species, followed by establishing and using a research and management fund, adapting to climate change, managing illegal resource use, waste and human impacts, as well as improving the captive breeding program for the iconic and critically endangered bird, curik Bali. Our approach may be useful for systematically comparing costed sets of management investments in other conservation areas worldwide.